PEREMPUAN DAN GREENWASHING DALAM PROMOSI AKUNTANSI KEBERLANJUTAN: ANALISIS SEMIOTIKA ROLAND BARTHES - Rusli, Urisnawati; Belo Ratte, Rosalena; Masnia, Masnia; Alimuddin, Alimuddin (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the representation of women in Unilever Indonesia's sustainability communication and to examine indications of greenwashing practices through Roland Barthes’ semiotic approach. The research focuses on two of the company's digital media channels: the official website and the Instagram account @unileveridn, with data spanning from January 2023 to March 2025. The analysis reveals that women are portrayed as agents of social change, empowered entrepreneurs, and symbols of environmental concern. Through visual symbols (such as the color green, environmentally friendly activities, and facial expressions), verbal narratives (keywords such as empowered and sustainable), and the structure of digital campaigns, a myth is constructed that associates women with a natural affinity for sustainability issues. This strategy reinforces the company's image as environmentally conscious and progressive on gender issues. However, the findings also indicate that some content prioritizes symbolic representation over concrete evidence or measurable impact, suggesting the potential presence of greenwashing. The company's sustainability communication appears to focus more on brand legitimacy than on reflecting transparent and ecologically or socially responsible business practices. This study recommends a critical evaluation of sustainability narratives that utilize female imagery, and urges companies to deliver communication that is data-driven and produces tangible impact.